Drying of Apple Slices in Atmospheric and Vacuum Freeze Dryer - Reyes-Salinas, A; Mahn-Osses, A (2011)
Atmospheric freeze drying (AFD) and vacuum freeze drying (VFD) of Fuji apples was investigated. A factorial design was used in each case, with particle size, freezing rate, infrared (IR) radiation, and air temperature as factors. The effect of these factors on moisture content, duration of drying, rehydration properties, color, and texture were determined. The drying curves were fitted with both the simplified constant diffusivity model (SCDM) and the modified Page model, and rehydration curves were tested with the Peleg model, resulting in R2 higher than 0.96. Antioxidant capacity, polyphenols, and ascorbic acid content in the final product were determined and compared with those obtained in a tunnel dryer. A sensory evaluation was performed. The drying times obtained for VFD were shorter than the drying times obtained for AFD. The particle size and IR application were found to be the significant parameters that affect duration of drying for both AFD and VFD (duration of drying was proportional to particle size and inversely proportional to IR application). Air temperature affected drying time only during the secondary drying stage. Estimated Deff values were on the order of 10-10 (m2/s). In AFD, R2 higher than 0.81 was obtained for the SCDM, and R2 higher than 0.96 was obtained for the Page model. In VFD, a better fit was obtained (R2>0.97) for both models. AFD produced nutritional alterations similar to convective drying. Sensory quality was not altered by AFD or VFD. © 2011 Taylor & Francis Group, LLC.